A Necessary and Sufficient Condition for Two-Person Nash Implementation - Dutta, Bhaskar; Sen, Arunava (Review of Economic Studies, 1991)
The main result of this paper is to characterize the class of two-person social choice correspondences which are Nash-implementable. The characterization result is used to formulate domain restrictions which allow the construction of non-dictatorial and Pareto-efficient social choice correspondences which are Nash-implementable.